TINJAUAN HUKUM PIDANA ISLAM TERHADAP PELAKSANAAN HUKUMAN MATI DI INDONESIA - Hasir Budiman Ritonga (Yurisprudentia: Jurnal Hukum Ekonomi, 2015)
The death penalty is still carried out in many countries, including Indonesia. Given the death penalty involves human lives, then many are going on the pros and cons in the community, each group has expressed the opinion statement from the perspective that they were proposing to become a protracted legal debate. but the Indonesian government together with some elements of society who support the death penalty remained on the establishment, that the death penalty should still be implemented to protect life. This paper seeks to inform some of the death penalty that has been implemented for a variety of specific criminal acts. This article tries to analyze, as far as the execution of cases that can be justified according to Islamic criminal law. Results of this paper shows that most such offenses can indeed be subject to the death penalty, there were still contain the controversy, but some are actually able to be released from death row because of the victim's family in a murder case has been forgiven